The Influence of Surgical Time Management, Drug Availability, Anesthesiologist Competence, Incident Reporting Systems, and Interdisciplinary Collaboration on Psatient Safety at Level II Iskandar Muda Hospital Banda Aceh - Syahrizal Ariandy; Lina Lina (International Journal Labs, 2025)
Patient safety during surgical procedures is influenced by several factors, including surgical time management, drug availability, anesthesiologist competence, incident reporting systems, and effective interdisciplinary collaboration. This study aims to analyze the impact of these five factors on patient safety at TK II Iskandar Muda Hospital in Banda Aceh, in order to provide comprehensive strategies for improving healthcare service quality. This study is a quantitative explanatory replication research conducted at Rumah Sakit Tingkat II Iskandar Muda, Banda Aceh, involving 115 medical personnel selected through purposive sampling. Primary data were collected via questionnaires and analyzed using multiple linear regression with SPSS 27, after validity, reliability, and classical assumption tests. This research analyzed factors influencing patient safety, revealing that effective operating time management, incident reporting systems, and inter-professional collaboration significantly enhance safety. Interestingly, increased drug availability showed a negative correlation with patient safety, indicating underlying supply chain management issues. While crucial, anesthesiologist competency did not show a statistically significant relationship in this study, possibly due to already high competency levels. Overall, improving patient safety requires a multi-factorial approach, focusing on incident reporting, collaboration, and operational efficiency, while addressing challenges in drug management.